Open-label, add-on trial of cetirizine for neuromyelitis optica. Issue 2 (March 2018) - Katz Sand, Ilana; Fabian, Michelle T.; Telford, Russell; Kraus, Thomas A.; Chehade, Mirna; Masilamani, Madhan; Moran, Thomas; Farrell, Colleen; Ebel, Shelly; Cook, Lawrence J.; Rose, John; Lublin, Fred D.
Abstract : Objective: This pilot study preliminarily examined the efficacy and tolerability of cetirizine as an add-on to standard therapy for neuromyelitis optica (NMO). Methods: Eligible participants met the Wingerchuk 2006 diagnostic criteria or had a single typical episode along with positive NMO immunoglobulin G. After baseline clinical and laboratory assessments, participants began treatment with cetirizine 10 mg orally daily, in addition to their usual disease-modifying therapy for NMO, and continued for 1 year. The primary end point was the annualized relapse rate (ARR) while on the same disease-modifying therapy before starting cetirizine compared with after taking cetirizine. Additional end points included disability (Expanded Disability Status Scale [EDSS]), relapse severity, tolerability, especially with respect to drowsiness measured by the Epworth Sleepiness Scale (ESS), and laboratory parameters. Results: The ARR before cetirizine was 0.4 ± 0.80 and after cetirizine was 0.1 ± 0.24 ( p = 0.047). There was no statistically significant difference in the EDSS (mean 3.9 ± 2.18 before the start of the study and 3.2 ± 2.31 at the conclusion of the study, p = 0.500). The ESS remained fairly consistent throughout the study (mean 6.5 ± 5.33 at baseline and 6.9 ± 4.50 at month 12, p = 0.740). Laboratory studies were unrevealing. Conclusions: In this pilot study, cetirizine was well tolerated, and the prespecified primary efficacy end point was satisfied. However, the open-label design and the small sample size of this pilot study preclude definitive conclusions. Further research is needed. Classification of evidence: This study provides Class IV evidence that in patients with NMO, the addition of cetirizine to standard therapy is safe, well tolerated, and reduces relapses.